Intentional and developmental learners"™ agency in deep learning processes during EFL writing: An explanatory sequential design - Rohadi, Tedi; Anugrah, Imani; Dedi, Sulaeman; Muhammad, Aminuddin; Shofia, Mardhiyah; Geng, Hui; Khan, Mohammad Ekramul Islam (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
This study investigates the extent to which EFL students demonstrate agency in deep learning processes during academic writing tasks, using an explanatory sequential mixed-methods design. Situated in the academic writing course at an Islamic university in West Java, Indonesia, the study involved 35 fourth-semester ELT students. Phase one utilized a self-report questionnaire to measure learners"™ perceived agency in planning, reflecting, making choices, transferring knowledge, and interacting with others. In phase two, semi-structured interviews explored students"™ lived experiences and behaviors across these dimensions. Quantitative results revealed generally high levels of perceived agency, particularly in goal-setting, strategy use, and reflection. Qualitative data enriched this picture, portraying that learners actively engaged with feedback, exercised autonomy in rhetorical decisions, and applied writing strategies across disciplines. The integration of findings highlighted that learner agency in writing is both intentional and developmental manifesting through personal effort, relational dialogue, and contextual adaptation. This study provides new insights by framing agency as both an intentional and developmental construct within deep learning processes"”an area that remains underexplored in EFL writing research. By explicitly linking learner agency with the mechanisms of deep learning, the study advances current understanding and calls for pedagogical approaches that scaffold autonomy, reflection, and knowledge transfer in EFL writing instruction. Keywords: academic writing, deep learning, EFL writing, learner agency, mixed-methods research How to cite this paper: Rohadi, T., Imani, A., Sulaeman, D., Aminuddin, M., Mardhiyah, S., Geng, H., & Khan, M. E. I. (2025). Intentional and developmental learners"™ agency in deep learning processes during EFL writing: An explanatory sequential design. Journal of English Language Teaching Innovations and Materials, 7(2), 1"“20. https://doi.org/10.26418/jeltim.v7i2.97197